Penerapan Teknologi Berbasis Iot (Internet Of Things) Dalam Pengumpulan Bukti Audit Di Masa Pandemi Covid-19 - Ramadhani, Nur Fitri; Triani, Ni Nyoman Alit (Badan Penerbit Universitas Muria Kudus, 2022)
The aim of this study is to obtain empirical evidence on how to apply IoT (Internet of Things) in collecting audit evidence during the COVID-19 pandemic to assist auditors in the audit process. The method used in this study is a qualitative method with interviews. The current pandemic requires auditors to use alternative audit evidence collection with IoT-based remote audit methods. The use of the right IoT system in audit evidence collection activities is very necessary with the aim that audit results have advantages and can be used as a reference in improving business processes and making quality decisions. The results show that the application of IoT is very helpful for auditors in the process of collecting audit evidence which is used as the basis for giving opinions in the audit process. However, not all audit collection procedures are carried out virtually, such as observation and inspection, both of which are carried out face-to-face as much as possible so that the auditor can ascertain what is actually happening in the field.